2020
DOI: 10.1016/j.nicl.2020.102446
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal white matter tract microstructure and 2-year language outcomes after preterm birth

Abstract: Highlights Preterm infant white matter tracts uniquely predict later toddler language. Neonatal medical history moderates posterior corpus callosum–language relations. Different associations by tract may relate to brain maturation and medical history.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 68 publications
1
16
1
Order By: Relevance
“…Another noteworthy consideration pertains to the role of the inferior longitudinal fasciculus in language, for the precise contributions of this tract to language remain underspecified ( Mandonnet et al, 2007 ). That said, recent longitudinal neuroimaging investigation among prematurely born infants observed that structural organization of the left inferior longitudinal fasciculus at the time of neonatal hospital discharge (within the first month of life, in a modest sample of 30 infants) is associated with subsequent toddler-age composite language abilities ( Dubner et al, 2020 ). Therefore, it is possible that non-significant effects for the left ILF may be attributed to a lack of variation in structural organization of this tract within the present sample, which could be at least partly due to investigation at a later stage in infancy (mean: 9 months) with typically developing infants born full-term, relative to the focus on newborn brain structure among infants born prematurely in the study by Dubner and colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another noteworthy consideration pertains to the role of the inferior longitudinal fasciculus in language, for the precise contributions of this tract to language remain underspecified ( Mandonnet et al, 2007 ). That said, recent longitudinal neuroimaging investigation among prematurely born infants observed that structural organization of the left inferior longitudinal fasciculus at the time of neonatal hospital discharge (within the first month of life, in a modest sample of 30 infants) is associated with subsequent toddler-age composite language abilities ( Dubner et al, 2020 ). Therefore, it is possible that non-significant effects for the left ILF may be attributed to a lack of variation in structural organization of this tract within the present sample, which could be at least partly due to investigation at a later stage in infancy (mean: 9 months) with typically developing infants born full-term, relative to the focus on newborn brain structure among infants born prematurely in the study by Dubner and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Methodological advances to conduct infant neuroimaging reveal that these dorsal and ventral pathways emerge within the first year of life ( Dubois et al, 2009 ; Leroy et al, 2011 ; Brauer et al, 2013 ; Dubois et al, 2016 ; Kostović et al, 2019 ). Longitudinal investigations of prematurely born infants reveal that properties of the left arcuate fasciculus, left inferior longitudinal fasciculus, and left superior temporal gyrus at full-term equivalent-age relates to subsequent toddler-age language abilities ( Aeby et al, 2013 ; Salvan et al, 2017 ; Dubner et al, 2020 ). This line of work has also importantly identified that alterations in language networks of the brain are associated with premature birth ( Thomason et al, 2017 ), which further illuminates the need for developmental studies of full-term infants to serve as a model for typical development.…”
Section: Introductionmentioning
confidence: 99%
“…First, T1 values are quantitative and have units that can be numerically compared across scanners, populations, and individuals 9 . Thus, our measurements in typically-developing infants provide a key foundation for large-scale studies of infant brain development in typical 38,39 and clinical populations such as preterm infants 40 , infants with cerebral palsy 41 , or fetal alcohol spectrum disorders 42 . Second, our methodology is translatable to clinical settings as it is performed during natural sleep.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative, track-specific analysis employs tractography to identify and segment the major WM pathways (Kulikova et al, 2015;Akazawa et al, 2016;Pecheva et al, 2017;Bastiani et al, 2019;Zollei et al, 2019;Kimpton et al, 2020;Dubner et al, 2020). In this case, the seed regions for tractography are defined in the template space and the segmentations of WM tracts are achieved by thresholding of the resulting probabilistic tractography maps.…”
Section: Running Titlementioning
confidence: 99%